NFTs and their possible use in the physical world - Preobraženskij, Alexej; Rejthar, Jan; Kučera, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
In 2021, the sudden surge in popularity of non-fungible tokens, commonly referred to as NFTs, caused a revolution in the digital art industry and gained a widespread media attention. However, this hype resulted in unrealistic expectations that proved unsustainable, leading to a decline in interest and widespread perception that NFTs were a dead-end. Despite this, new applications continue to emerge, drawing in fresh audiences. This thesis aims to explore unconventional perspectives and propose potential use cases that demonstrate how non-fungible tokens can enhance our physical world and improve our lives in the future.
Vedoucí práce: Jan Rejthar
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses